Quality of Visit and Fulfillment Needs after Childbirth: Study on Postpartum Maternal Mortality - Mariana Ngundju Awang; Diyan Maria Kristin (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2020)
Most maternal deaths occur during the postpartum period so that childbirth health services play an important role in reducing maternal mortality rates from 6 hours to 42 days after giving birth. It is estimated that 69% of maternal deaths due to pregnancy occur after childbirth, and 50% of postpartum deaths occurred in the first 24 hours. The highest number of maternal deaths was found in East Sumba Regency which was 19 maternal deaths, 12 of which were maternal deaths during the puerperium. Maternal deaths in 2017 out of 9, there were 5 postpartum mothers whereas the 3rd postpartum visit was 91%. The objective of this study is to determine the quality of puerperal visits and the fulfillment of the needs of puerperal women in East Sumba Regency in 2015-2018. This type of research is qualitative research with a phenomenological study. Participants or informants in this study were the husband or family of all mothers who died postpartum in 2015-2018 and midwives who deal with these mothers during antenatal care, childbirth, and postpartum as well as data analysis which is content analysis. The results showed that the quality of puerperal visits was still irregular, systematic, and unfocused so that it was unable to detect postpartum problems early. Meeting the needs of mothers during childbirth is still incomplete, not detailed, and does not routinely conduct head-to-toe examinations during postpartum visits. The conclusion of the study shows that the quality of the visit and the fulfillment of the needs of the postpartum mothers are related to maternal mortality during the postpartum period in East Sumba Regency.